Green economy and its future - Atta ul Mustafa; Haleema Afzal; Zunaira Zahoor (Goodwood Publishing, 2021)
Purpose: This paper tries to find out the current progress of subjective developed and developing countries regarding green economy development. Research Methodology: This paper uses a graphical radar approach to show countries' overall performance toward the green economy. Results: This paper concluded that developed countries are ahead of developing in terms of current health expenditure, large forest area and tons of national parks. However, they are on the same page in terms of pollution, whether it is air or solid. Limitations: Several elements restrict this study. The study is carried out in chosen underdeveloped countries and developed ones. The position of the countries is therefore restricted. Consequently, the results and outputs may not apply to geographical sites. Because of unavailability, this study sample may not be sufficient. Contribution: This study will benefit both developed and developing countries by providing a clear understanding and scenario about the green economy, well-being, and green infrastructure. The findings of this study will be beneficial to institutions, researchers, politicians, the government, and others. Governments and government agencies can plan and promote their strategies and policies to understand green infrastructure and its impact on human health clearly. This study further extends the literature on the green economy and provides a new way of measuring it through its different components. Furthermore, this study can help explain where we stand right now and where we should set sail to.